RESEARCH ON THE FINANCIAL ASPECTS OF SOLAR POWER PROJECTS IN THE RENEWABLE ENERGY INDUSTRY - ARULALAN M.; RAJINDER SINGH (Innovative Research Thoughts, 2022)
The usage of energy on a global scale is only going up from year to year. Both nonrenewable fossil fuels and renewable sources of energy, such as the sun, the wind, biomass, and hydropower, may be used to generate electricity. These days, fossil fuels are the primary contributors to the creation of electricity all around the globe. The increasing depletion of fossil fuels has major unintended effects, one of which is an increased threat to the environment posed by climate change. A greater awareness of the risks to the environment and the need for a sustainable energy supply have both contributed to the emergence of the discussion on the increased use of renewable energy sources.